The implied significance of integrative geographical information systems in sustainable tourism and comprehensive community development in Musina Municipality, South Africa. Issue 1 (15th November 2021) - Ramaano, Azwindini Isaac
Abstract : Purpose: The purpose of the paper was to explore the latent function of geographic information systems (GIS) in sustainable tourism, community-based natural resource management (CBNRM) and local community development in Southern Africa, broadly Africa, and diverse rural areas elsewhere globally. Hence, significantly liaising with data and literature review on the Musina Municipality natural resource management, livelihoods, and tourism development issues in Limpopo Province, South Africa. Design/methodology/approach: The study utilizes a general literature review, document reviews, focus group discussions and field observations to examine the Musina Municipality's rural, environmental and tourism resources management situations along with African and worldwide pertinent implications. The study benchmarks with CBNRM and GIS in sustainable tourism nature within the Musina Municipality. Findings: The study reveals a fitter dormant-synergetic link among tourism and agrarian (rural) exercises that GIS along a concept of CBNRM can expand within the Municipality. Hence, the study has presented a necessity for a proper and a GIS-unified tourism approach to permit the local communities in Musina Municipality and towards the entire continent. Originality/value: Several rural populations in Southern Africa and Africa broadly dwell in low-income areas; Musina Municipality is no exception. Such environs are rich in natural biodiversity, including tourism entities host regions. GIS, sustainable tourism and CBNRM can create a gestalt of local community development projects within such milieus.